Pasar Uang dan Kurva LM: Tinjauan Konvensional dan Perspektif Ekonomi Islam - Akhus Nur Salim; Alif Ghufron Al-Fattah; Adnan Wijaya; Suci Hayati (Indo Publishing, 2025)
This study aims to analyse the concept of money market and LM curve in the perspective of conventional economics and Islamic economics. The method used is library research by reviewing various scientific literature, journals, and relevant official documents. In conventional economics, the money market functions as a means of providing short-term liquidity through interest-based instruments, and the LM curve describes the relationship between interest rates and national income in a money market equilibrium. In contrast, the Islamic economy rejects the practice of usury and makes money solely a medium of exchange, so the Islamic money market uses profit-sharing-based instruments and the principle of fairness in transactions. The LM curve model in Islamic economics needs to be reformulated with a non-usury approach that is in accordance with maqashid sharia. The results of the study show that the difference in basic principles between the two approaches creates a different money market system structurally and normatively. Therefore, understanding these two perspectives is very important in developing an inclusive, fair and sustainable financial system.